PENGARUH SALURAN DISTRIBUSI DAN POTONGAN HARGA TERHADAP MINAT BELI KONSUMEN PADA CV MITRA CAHAYA NAULI PANDAN - Sri Rahayu Nazara; Kaharuddin; Nelly A.Sinaga (Universitas Sains dan Teknologi Komputer, 2022)
The purpose of this study was to identify and analyze the influence of distribution channels and price discounts on consumer buying interest in CV. Nauli Pandan Light Partners. The research hypothesis is that distribution channels and price discounts simultaneously have a positive effect on consumer buying interest in CV. Nauli Pandan Light Partners. The population is 59 and used as a sample. Data collection techniques using interviews, observation and questionnaires. Data were analyzed using descriptive statistics. The results of the study found that distribution channels and price discounts simultaneously had a positive effect on purchase intention, where Fcount (49.788) was greater than Ftable (3.15) or (49.788 > 3.15). Partially the distribution channel variables influence purchase intention, where the t-count value is 3.650 > ttable value 2.001 or significant (Sig-t) of 0.001 < α (0.05). Partially the price discount variable has an effect on buying interest, where the t-count value is 3.794 > t-table value of 2.001 or significant (Sig-t) of 0.000 < α (0.05) The calculation result of the coefficient of determination R Square is 0.627 means 62.7% channel distribution and price discounts can affect purchase intention, while the remaining 37.3% can be influenced by other factors not discussed in this study.